Perancangan User Experience Aplikasi Mobile Peminjaman Buku Online menggunakan Pendekatan Human-Centered Design (Studi Kasus : Rumah Baca Cerdas Malang) - M. Hamaas Taqiyuddin A.; Herman Tolle; Fais Al Huda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Book lending is a service that enables customers to make the best possible use of the library's holdings. However, several libraries that lend books have been shuttered as a result of the large number of instances of Covid-19 distribution.. Due of the restricted availability of books for borrowing, adaptive methods are required to combat the Covid-19 epidemic in the modern digital age. With response to these issues, a mobile application for online book lending was created in the goal of resuming online book lending. The application provides lending services for both paper and digital books. This program was designed in collaboration with stakeholders that lend books in Malang, namely the Rumah Baca Cerdas Malang. To provide a positive user experience, a Human-Centered Design method is employed, which focuses on the broad user's requirements and involves stakeholders and potential users. Usability and user experience tests were used to evaluate the solution design with ten individuals. The effectiveness of the usability test is 88.6 percent, the efficiency is 0.131 goals/second, and the user satisfaction is 88.5 percent with an A grade. The findings of user experience testing conducted using the user experience questionnaire (UEQ) achieve good benchmark scores in all categories, including attractiveness 2.52, clarity 2.65, efficiency 2.53, accuracy 2.48, stimulation 2.38, and novelty 1.70..